PELATIHAN LITERASI DIGITAL DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 DI DESA PAGERAGUNG - Kusuma, Jaka Wijaya; Khaeruman, Khaeruman; Tabroniz, Tabroni; Hanafiah, Hafidz; Dewi, Irma Nurmala (Yayasan Education and Social Center, 2025)
The digital literacy training in Pageragung Village aims to improve the community's skills in facing the challenges of the Industrial Revolution 4.0. With the rapid development of technology, rural communities are faced with the need to understand and utilize digital technology in order to access information, public services, and economic opportunities through e-commerce.The training covers an introduction to the basic use of digital devices, the use of social media for promotion, and an introduction to e-commerce to increase income. The results of this training show that most participants have gained basic skills in using digital devices, utilizing social media for promotion, and an introduction to e-commerce to increase income.This training covers the basics of using digital devices,utilizing social media for promotion, and an introduction to e-commerce toincrease income. The results of this training show that mostparticipants experienced a significant increase in their ability to usedigital technology, despite challenges related to limited internet infrastructure. This program also succeeded in opening up economic opportunities forthe village community through the use of digital platforms. However,the sustainability of this training requires assistance and improved internet accessso that its benefits can be felt more widely. In conclusion, this traininghas succeeded in empowering the people of Pageragung Village to face the digital era,but requires better infrastructure support toensure long-term success.